Effect of Season on Hampshire Crossbreed Boar Semen Quality and Antioxidant Status under Hot Humid Sub Tropical Climate - Singh, Mahak; Celina, Apani; Nguillie, Ebibeni; Katiyar, Rahul; Deori, Sourabh; Chamuah, Jayanta; Kalita, Homeswar; Kumar Mishra, Vinay (The Indian Journal of Animal Reproduction, 2025)
The present investigation aimed to study the season’s effecton semen quality,and antioxidant status of Hampshire cross bred boar in sub-tropical climatic condition. For the present experiment, same six Hampshire crossbreed boars were  used in summer and winter season. Sperm quality parameters (SQPs) were assessed microscopically. Computer-assisted  semen analysis (CASA) was used to assess sperm kinematics. Antioxidants biomarkers (glutathione peroxidase; GPx,  catalase; CAT, total antioxidant capacity; TAC) and lipid peroxidation (malondialdehyde; MDA) were measured in boar’s  seminal plasma. Summer season had significant (p < 0.01) negative effect on reaction time and false mounts. Semen  volume and sperm concentration was recorded to be significantly (p < 0.01) higher in winter season. Sperm total motil ity, progressive motility, viability, acrosomal integrity and HOST reactive sperm were recorded to be significantly (p
Keywords: Boar; Heat Stress; Semen Quality; Antioxidant; Biomarkers; Sub-Tropical